Evaluating the Impact of GenAI in High School Education: A Critical Review - Zebua, Nofamataro (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
GenAI has currently been widely integrated into learning in secondary schools, as it is considered to provide the potential to enhance the learning experience for students. However, using GenAI in secondary school settings remains controversial, as its benefits coexist with significant ethical, social, and educational challenges. This review critically examines the role of GenAI in secondary school education, assessing current applications, potential educational benefits, and unique challenges. Through the exploration of case studies and empirical research, the researcher highlights key areas where GenAI can enhance learning while presenting possible drawbacks and ethical dilemmas. The researcher concludes by suggesting guidelines for the responsible integration of GenAI in secondary school education, aiming to capitalize on its potential while addressing critical risks.